2009
DOI: 10.1289/ehp.0800012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome Associated with Body Burden Levels of Dioxin and Related Compounds among Japan’s General Population

Abstract: BackgroundEnvironmental exposure to some persistent organic pollutants has been reported to be associated with a metabolic syndrome in the U.S. population.ObjectivesWe evaluated the associations of body burden levels of dioxins and related compounds with the prevalence of metabolic syndrome among the general population in Japan.MethodsWe conducted a cross-sectional study with 1,374 participants not occupationally exposed to these pollutants, living throughout Japan during 2002–2006. In fasting blood samples, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 32 publications
12
93
0
5
Order By: Relevance
“…However, when congeners of PCBs were assessed separately, only the 118 and 126 DL-PCB congeners showed a positive and significant association. Moreover, Uemura et al, 6 who evaluated only the DL-PCBs among general Japanese population, observed an adjusted odds ratio for hypertension of 1.9 (95% CI, 1.1-3.1) and P for trend <0.01 for the highest quartile of DL-PCBs versus the first quartile.…”
Section: Discussionmentioning
confidence: 99%
“…However, when congeners of PCBs were assessed separately, only the 118 and 126 DL-PCB congeners showed a positive and significant association. Moreover, Uemura et al, 6 who evaluated only the DL-PCBs among general Japanese population, observed an adjusted odds ratio for hypertension of 1.9 (95% CI, 1.1-3.1) and P for trend <0.01 for the highest quartile of DL-PCBs versus the first quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with the reported association of coplanar PCB exposure and metabolic syndrome (Uemura et al, 2009), this highlights an important area for future risk assessment.…”
mentioning
confidence: 83%
“…The purpose of this project is to collect data on blood levels and the dietary intake of dioxins and other chemical substances and their determinants in Japanese populations without occupational exposure 12,13) . The surveys were carried out in five regional blocks: Hokkaido/Tohoku, Kanto/Koshin-etsu, Tokai/Hokuriku/ Kinki, Chugoku/Shikoku, and Kyushu/Okinawa.…”
Section: Study Subjectsmentioning
confidence: 99%